Trauma Facial - Aplicativo Com Protocolo De Atendimento Ao Paciente Com Traumatismo Facial Para Unidades De Saúde De Atenção Primária - Moller, Mathias Alberto [UNIFESP] (2017)
The work of thought represented here investigates the notion of Aufklärung in the political texts of Immanuel Kant. Since the launching presentation of the question “What is Enlightenment”, Kant´s minor text published by the Berlinische Monatsschrift in December 1784 is inserted in an arch of dissonant considerations about a word that in that time already couldn´t be understood without a comment. Being so, and under the consideration of the Brazilian reception, addressed by Rubens Rodrigues Torres Filho, the Kantian text is made more understandable when restored to its direct context. In result, a given reconstruction of the original debate reveals the Monatsschrift as a main organ for the German Enlightenment to the publication of texts in a popular tone besides a means of disclosure of the debates engaged under the seal of the secret Wednesday Society. In this respect, the enlightenment motto sapere aude employed by Kant in Latin for his definition of exit of mankind´s immaturity imposes the investigation of its meaning and presents the Kantian proposal of Aufklärung as strive to wisdom. In fact, doing so aimed at indicating the hypotheses that an interpretive view and even its own options of translation would already announce a philosophical position. For that, the presentation of the available translations to Portuguese permits to envisage its terminological options and its possible philosophical endeavor. A position upon which it is here sustained the tension between formulating the question and its continuous answering in search for the signification of meaning.